Bodies Without Borders
XXI, 204 p.
Keywords: Globalization is often thought of as an abstract process that happens "out there" in the world. But people are ultimately the driving force of global change, and people have bodies that are absent from current conversations about globalization. The original scholarly research and first-person accounts of embodiment in this volume explore the role of bodies in the flows of people, money, commodities, and ideas across borders. From Zumba fitness classes to martial arts to fashion blogs and the meanings of tattooing, the contributors examine migrating body practices and ideals that stretch across national boundaries.